Kriminologi Kejahatan Bisnis dan Pertanggungjawaban Perseroan Terbatas dalam Hukum Pidana - Syah Awaluddin; Indri Sukiman; Muh. Sanusi Rumbara; Abdul Rasid Waliulu (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2022)
Unclear criminal liability regulations for limited liability companies are the main obstacle in eradicating criminal acts committed by limited liability companies. This study focuses on the study of the urgency of regulating criminal liability for limited liability companies in their business activities through a criminology approach. The criminology study in this study uses several theories such as Strain Theory, Social Control Theory, Opportunity Theory, and Work Ethic Theory to analyze the factors that encourage limited liability companies to commit crimes. This study uses a normative legal research method that is descriptive analytical with a statutory approach, case approach, and conceptual approach. The results of the study conclude that the regulation of criminal liability and the imposition of criminal penalties on limited liability companies is urgent because the current regulation of criminal liability has not been able to fulfill the objectives of the law, namely certainty, justice, and benefit, and is a legacy of the colonial era that does not recognize limited liability companies as subjects of criminal law. As an update, Law Number 1 of 2023 seems to be able to answer the challenge of the urgency of criminal liability for limited liability companies as subjects of criminal law, which is stated in Articles 45 to 50 which regulate corporate criminal liability.